THE CORRELATION BETWEEN STUDENTS’ SELF CONFIDENCE AND THEIR SPEAKING SKILL AT THE TWELFTH GRADE OF SMA N 2 BUKITTINGGI - Sari, Riva Silvia; Dewi, Merry Prima (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2021)
The design of this research was correlational research. This research aimed to find out the correlation between students’ self-confidence and speaking skills at the twelfth grade of SMA N 2 Bukittinggi. The background of this research was there were several problems related to students’ self-confidence, and those problems were contrary to the theory. The population of this research was all of the twelfth-grade students of SMA N 2 Bukittinggi in the academic years of 2020/2021, which consists of 8 classes. The sample was 28 students taken by simple random sampling technique. The research results showed that there is a correlation between students’ self-confidence and their speaking skill. The researcher found that the coefficient of correlation between students’ self-confidence and their speaking skill was 0,286. There was a positive correlation and significance. It means that Ho is accepted. Thus, there is a positive correlation between students’ self-confidence and speaking skills at the twelfth grade of SMA N 2 Bukittinggi.